The benefits of Pilates in the gestational period: an integrative review (Research, Society and Development, 2022)
Pregnancy is considered a unique physiological window through maternal and fetal adaptations resulting in a major long-term health impact. The usual problems in pregnancy are treated in different ways, among these the safest, most appropriate and economical to eliminate their complications, is to improve health and quality of life, as well as the regular practice of exercises. Among the various types of exercise, the Pilates method is highlighted, providing the individual with respect and self-knowledge of the body, acting in the physiological preparation and confidence of the practitioner, encompassing the quality of breathing, strengthening, stretching the body structure and body proprioception. This is an integrative literature review, through consultation in online databases to collect information. The main journal databases used for active article searches are: ACOG, Scielo, PubMed, LILACS, MEDLINE, UFG, UFRGS, Google Scholar. Over the years, the practice of physical exercise and kinesiotherapy are the main physiotherapy strategies, applied as non-pharmacological therapies for various pathologies. Pilates is internationally evidenced as one of the fundamental exercises to improve physical-mental and motor function, including a series of low pressure activities that increase the flexibility and strength of the body. It was concluded that the Pilates method is pointed out as of great applicability, through its benefits to pregnant women according to their needs, it is an exercise that adapts to the development of pregnancy and affects the musculoskeletal, cardiovascular and respiratory systems.